Why do mothers attending a baby-friendly mother and child health care unit start early solid food to their babies? [Bebek dostu bir ana çocuk saǧliǧi merkezinden hizmet alan anneler neden bebeklerine erken ek gida vermeye başliyor?] - (:unkn) unknown (Kare Publishing, 2008)
Aim: WHO strictly recommends breastfeeding of new-borns exclusively for the first 6 months. This study aims to explore timing and reasons of the mothers who took service from a baby-friendly mother and child health care unit, to start complementary foods. Material and Medhod: For a six week period 358 mothers visiting the baby friendly Mother and Child Health Care Center that was chosen for this descriptive study were interviewed. A structured questionnaire that included open and close ended questions was used. For the babies older than 6 months, the questions about using feeding bottles and pacifiers were asked directing the first 6 months. Data was collected by the same researcher and by face to face interviews. Chi-square, student's t test, Mann Whitney-U analysis were used. Results: Although %98,9 of the mothers were breast feeding after delivery, %44,6 started complementary foods before 6 monthsand the most frequent starting period was 0-3 months. Starting solid foods before six months was significantly related with being term, using pacifiers and feeding bottles before six months and feeding the baby with formula just after birth at the hospial. Conclusions: Besides the high frequency of breastfeeding, mothers begin to give solid foods in an early period. During well baby follow-ups mothers should be educated earlier about appropriate timing of complementary foods, especially preterm babies' mothers should be supported about appropriate feeding and mothers should be recommended not to use pacifiers and feeding bottles.
Keywords: Baby-friendly; Breastfeeding; Solid food